Immune tolerance, a walk through time: How does the immune system differentiate between self and foreign? (2013)
Since the first studies in immunology, there has been a clear need to understand how, under normal conditions, the immune system tolerates its own antigens and attacks some foreign antigens that it perceives as potentially dangerous and how, in certain circumstances, the loss of tolerance triggers autoimmune diseases. It has been over half a century since Billingham, Brent and Medawar demonstrated, in an experimental model, the mechanisms involved in the development of immunological tolerance. Since then transplant immunologists have intensively investigated the mechanisms involved in maintaining tolerance, in the hope of avoiding the complications of non-specific immunosuppression, as well as the prevention of chronic rejection. An important characteristic was observed by Medawar, who argued that during transplantation an individual's immune system is tolerant to transplanted tissue, maintaining the response to other antigens. Recent studies have shown that loss of tolerance to transplantation is associated with a hyper-response to antigens of the transplanted tissue; a problem that has plagued clinical immunologists, who have focused their efforts on developing accurate measurement systems to enable them to measure how an individual could be tolerant to transplant. Attempts to induce tolerance in the individual are based on understanding the basic mechanisms of tolerance, in which there has been significant progress. This growth in knowledge has been in parallel with a better appreciation of the complexity of immune tolerance. In particular, progress has been made in understanding the essential role of tolerogenic dendritic cells (CDS) and the maintenance of tolerance by regulatory T cells. © 2013 Asociación Colombiana de Reumatología. Published by Elsevier España, S.L. All rights reserved.